ANALISIS TEORITIS PENGGUNAAN JENIS TURBIN ANGIN TERHADAP OUTPUT DAYA LISTRIK (Department of Mechanical Engineering, Faculty of Engineering, Universitas Negeri Semarang, 2022)
Wind turbine is a tool that converts kinetic energy into electrical energy. For now it is important to improve the efficiency of wind power plants in generating electrical power through the use of wind turbines. Seeing the rapid growth of the human population, the need for energy has also increased drastically. But that population growth is not offset by the availability of energy. Because for now the availability of energy in Indonesia, in particular, still uses energy resources that cannot be renewed. Seeing these shortcomings can take a solution with the use of alternative energy derived from nature, one example is wind energy. The purpose of this study is to find out how much electrical power output from the use of wind turbine types. This research uses the literature study method by examining 15 journals or sources related to research. The data used in this study were taken from documents or sources related to the study.